Pelatihan Studi Kelayakan Unit Usaha BUMNag Kamang Hilia Kabupaten Agam Provinsi Sumatera Barat: Feasibility Study Training for BUMNag Business Units in Kamang Hilia, Agam Regency, West Sumatra Province - Pebriyani, Dewi; Fitra, Halkadri; Sulaiman S, Ahmad Rahbani; Hayati, Dian Indah; Fawziah, Intan Nurbaiti; Taqwa, Salma; Putra, Rino Dwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The feasibility study training program for BUMNag Kamang Hilia, Agam Regency, West Sumatra, was designed to enhance the capacity of village officials, BUMNag managers, and the local community in planning, analyzing, and developing business units that leverage local potential. This training emphasized the importance of well-structured and data-driven business planning before establishing or expanding business units, thereby increasing the likelihood of success and reducing potential risks. The materials combined theoretical concepts with practical applications, covering the fundamentals of feasibility studies and analyses of market, technical, managerial, legal, social, and financial aspects. Participants were also trained in conducting risk assessments and preparing feasibility recommendations. A participatory learning approach was adopted through group discussions, case studies, document preparation simulations, and presentations, enabling participants to apply their knowledge directly to real local business opportunities. The training significantly improved participants' knowledge and analytical skills, fostering more professional BUMNag management. In the long term, it is expected to generate economically viable business units, optimize local resource utilization, and contribute to the economic independence of the nagari.